FATWĀ IN CONTEMPORARY ISLAMIC JUDICIARY: THE ACCOMMODATION OF MUI FATWĀ AMONG JUDGES OF INDONESIAN RELIGIOUS COURT - Abdullah Jarir; Nina Chairina; Masduki; Abdul Rahim Hakimi (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2025)
Purpose – This study focuses on the extent to which the application of MUI ( Council of Indonesian Ulama) fatwā in the Indonesian Religious Court, particularly in the context of Islamic family law. This issue has led to discursive debates between Indonesian ʿUlamāʾ and some scholars.  Some argue that fatwā is not binding because it is not a legal source and there is no fatwā in the hierarchy of Indonesia’s legal system. However, MUI fatwās have been used as a legal basis for decisions related to Islamic family law in the Indonesian Religious Court. Method - This research uses sociological jurisprudence as a method for inquiry. This method is based on normative legal research. However, it does not discuss the legal system or regulation; nevertheless, it observes the reactions and interactions that occur in society when the regulation is enforced.  Findings – This study concluded that although MUI fatwā is not binding in the Indonesian Legal system, the judges of the Indonesian Religious Court have considered the MUI fatwā as a legal basis in rendering decisions relating to Islamic family law. In other words, the fatwās issued by the Majelis Ulama, which have been used as a legal basis by judges in the Religious Courts for several cases related to Islamic family law in Indonesia, will shift. The issues mentioned deal with the legal status of children out of wedlock, child adoption, interfaith marriage, and Ahmadiyah followers. Research contribution – This study reveals the role of MUI fatwas as a non-formal source of legal legitimacy that, while not legally binding, continues to influence judicial practices in Indonesian Religious Courts concerning Islamic family law. Originality/value – The value of this research rests in its ability to demonstrate the dynamic interaction between religious authority and the positive legal system, thereby opening a broader discourse on the integration of fatwas into national legal practice.